Exploring Wireless Power Transfer through configuration topology and field beam - Hafiz, Sabihul (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Wireless Power Transfer (WPT) have been popularized to the industry and academia researchers. This is because of its efficient battery charging system for most of the electronics appliances, house hold electronic gadgets, electronic vehicles and biomedical applications. The WPT transmission is favourable because it is hassle free, efficient, low cost, reliable, user, eco–friendly and considerably green technology. Researches have been investigating and suggesting its advanced charging methods to make wireless power transmission more efficient toward general users.. However, most of the existing methods have facing the challenges for various applications. Consequently, to cater issue and optimize the efficiency, this study scrutinises the previous methods and come out with new proposal. The proposed method develops and configures the series to series, series to parallel, parallel to series and parallel to parallel topologies for different applications with diverse power transmission levels. Moreover, this study also explores the output voltage, power, and efficiency through the topology configurations. The performance of the proposed model is assessed using MATLAB and PSPICE tools. The analytical results are also then empirically tested. As a result, the achieved results suggested that the output power and efficiency at the same frequency is dependent on load variation and coupling efficiency. It is also found from the simulation result that the output efficiency has been improved by the proposed configuration. Moreover, it's been assessed that the efficiency is maximized through the proposed model.